Closed-loop intracranial stimulation alters movement timing in humans - Moore, Bartlett D.; Aron, Adam R.; Tandon, Nitin (Brain stimulation, 2018)
A prime objective driving the recent development of human neural prosthetics is to stimulate neural circuits in a manner time-locked to ongoing brain activity. The human supplementary motor area (SMA) is a particularly useful target for this objective because it displays characteristic neural activity just prior to voluntary movement. Here, we tested a method that detected activity in the human SMA related to impending movement and then delivered cortical stimulation with intracranial electrodes to influence the timing of movement. We conducted experiments in nine patients with electrodes implanted for epilepsy localization: five patients with SMA electrodes and four control patients with electrodes outside the SMA. In the first experiment, electrocorticographic (ECoG) recordings were used to localize the electrode of interest during a task involving bimanual finger movements. In the second experiment, a real-time sense-and-stimulate (SAS) system was implemented that delivered an electrical stimulus when pre-movement gamma power exceeded a threshold. Stimulation based on real-time detection of this supra-threshold activity resulted in significant slowing of motor behavior in all of the cases where stimulation was carried out in the SMA patients but in none of the patients where stimulation was performed at the control site. The neurophysiological correlates of impending movement can be used to trigger a closed loop stimulation device and influence ongoing motor behavior in a manner imperceptible to the subject. This is the first report of a human closed loop system designed to alter movement using direct cortical recordings and direct stimulation. •In humans, the supplementary motor area manifests characteristic neural activity just prior to voluntary movement.•We developed a closed-loop deep brain stimulation system capable of detecting this activity and stimulating the SMA before movement occurs.•Stimulation based on closed-loop detection of SMA activity resulted in significant slowing of behavior.•Stimulation using an identical protocol outside the SMA did not result in significant slowing of behavior.•This is the first report of a human closed loop system that alters movement using direct cortical recordings and stimulation.